Effects of estuarine water mixing on the mobility of trace elements in acid mine drainage leachates. (February 2023) - Pérez-López, Rafael; Millán-Becerro, Ricardo; Basallote, María Dolores; Carrero, Sergio; Parviainen, Annika; Freydier, Rémi; Macías, Francisco; Cánovas, Carlos R.
Abstract: This research reports the effects of pH increase on contaminant mobility in acid mine drainage from the Iberian Pyrite Belt by seawater mixing in the laboratory, simulating the processes occurring in the Estuary of Huelva (SW Iberian Peninsula). Concentrations of Al, Fe, As, Cu and REY in mixing solutions significantly decreased with increasing pH. Schwertmannite precipitation at pH 2.5–4.0 led to the total removal of Fe(III) and As. Subsequently, iron-depleted solutions began to be controlled by precipitation of basaluminite at pH 4.5–6.0, which acted as a sink for Al, Cu and REY. Nevertheless, as the pH rises, schwertmannite becomes unstable and releases back to solution the previously retained As. Moreover, other elements (S, Zn, Cd, Ni and Co) behaved conservatively in mixing solutions with no participation in precipitation processes. Some toxic elements finally end up to the Atlantic Ocean contributing to the total pollutant loads and environmentally threatening the coastal areas. Graphical abstract: Unlabelled Image Highlights: Mining contaminants released from Iberian Pyrite Belt reach estuarine environments. S, Zn, Cd, Ni and Co remained mobile during seawater mixing even at pH 7. Non-conservative Al, Fe, Cu and REY undergo precipitation and sorption processes. First adsorption and then desorption of As took place from Fe precipitates. Mining-related pollutants contribute highly to the contamination in Estuary of Huelva.